STRATEGI PENGEMBANGAN USAHA KECIL DAN MENENGAH BERBASIS EKONOMI KREATIF DI KOTA PARIAMAN - Arivetullatif Arivetullatif; Gema Ardina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
MSMEs are individual businesses or individual business entities that have met the criteria for micro-enterprises. Pariaman has 7,839 MSMEs located in Pariaman, a total of 7,839 for all types of MSMEs, ranging from micro, small to medium. The purpose of this study was to find out how the strategies and inhibiting factors of the Office of Cooperatives and Micro Enterprises in the development of micro, small and medium enterprises based on the creative economy in Pariaman City. This study uses descriptive qualitative data analysis techniques according to the data obtained by researchers in the field. Data obtained in the form of words, pictures, notes, documents and interviews. The analytical method used in this research is SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) by monitoring internal and external factors. The results of the study using SWOT analysis and strategies that can be used by the Pariaman City Micro Business Cooperative Office are as follows: a.) The strategy formed from the internal strengths and weaknesses (Strength-weakness) is to increase the integrated business service center in developing micro-enterprises for consulting business actors in Kota Pariaman, increasing additional budget and human resources for training business actors in Kota Pariaman. b) The strategy formed from the external factors of opportunities and threats (Opportunity-Threat) is to increase the implementation of supervision on business actors and increase understanding of patents and laws for the products of business actors in Kota Pariaman.Keywords: Strategy, Development, SWOT.